Biomedical Significance of Hormesis - Musharraf B. Avliyoqulova; Nargiza R. Hamzayeva (Peerian Journals Publishing, 2022)
Hormesis is a two-phase dose response with specific quantitative characteristics for the amplitude and width of stimulation. It is highly generalized and independent of the biological model, endpoint, causative agent, biological organization level, and mechanism. Hormesis can be triggered by direct stimulation or by over-compensation for disruption of homeostasis. Induction of hormesis by low-level stressors not only rapidly regulates adaptive processes to repair damage, but also protects the adapted system from damage due to the next difficult dose (toxic) in a defined temporal window. The remarkable consistency of the amplitude of the hormetic reaction gives a quantitative description of the biological plasticity of the hormesis. Knowledge of hormesis has particular potential biomedical significance in slowing or slowing down normal aging processes and the development of severe diseases.
Keywords: Hormesis; ageing process; diseases; curcumin; aerobic exercises